Messenger RNA Expression of Selected Factors at Different Sites of the Bovine Endometrium Associated With Uterine Health - Pothmann, Harald; Flick, Paula; Tichy, Alexander; Gabler, Christoph; Drillich, Marc (Frontiers in Veterinary Science, 2021)
Recent studies have elucidated the role of several pro-inflammatory factors as mediators of inflammatory processes in the bovine endometrium. Only few studies, however, have analyzed samples collected from different regions of the uterus of the same animal. We followed the hypothesis that with increasing severity of the disease differences in mRNA expression of the selected genes between sampling sites decrease because the inflammation becomes generalized throughout the uterus. Thus, the objective was to assess the mRNA expression of uterus-associated pro-inflammatory factors at five pre-defined endometrial sites, i.e. corpus uteri, left horn base, left horn tip, right horn base, and right horn tip, in cows with clinical and subclinical endometritis and in healthy controls. We analyzed the mRNA expression of interleukin 1A, interleukin 1B, chemokine ligand 8, prostaglandin-endoperoxide synthase 2, protein tyrosine phosphatase receptor type C, carcinoembryonic antigen related cell adhesion molecule 1, and mucin 4 and 16. Based on vaginoscopy and endometrial cytology (≥ 5% polymorphonuclear neutrophils) between 28 to 34 days in milk, 18 Simmental cows were categorized in clinical endometritis (n = 7), subclinical endometritis (n = 4), and healthy group (n = 7). In general, the analyses revealed a great variation of mRNA expression between sites and animals. Multiple sampling did not result in significant difference of mRNA expression between the five different endometrial sites and was independent of the uterine health status (P > 0.05). This indicates that inflammatory processes can be regarded as diffuse or throughout the uterus. Thus, our hypothesis had to be rejected.